Impact of GST on HDB households in Singapore. - Kuek, Hsiao Feng. (2013)
The emergence of the Value-Added Tax/Goods and Services Tax has evoked many debates and arguments all over the world. Many studies have been conducted to look into GST-related issues. The main objective of this study is to explore the impact of GST on HDB households. The study endeavours to find out if GST has an effect on the spending habits and lifestyles of Singaporeans.